Biocompatibility evaluation, wettability, and scratch behavior of Ta-coated 316L stainless steel by DC magnetron sputtering for the orthopedic applications - Pathote D.; Kumari P.; Singh V.; Jaiswal D.; Gautam R.K.; Behera C.K. (My University, 2025)
As 316L stainless steel is widely used in manufacturing biomedical devices such as hip joints, screws, and plates, these devices are likely to fail soon after implantation due to inadequate biological reactions. To address these issues, a coating was deposited on 316L SS to increase biocompatibility and hydrophilicity. Tantalum (Ta) coating for 15, 30, and 60 min (1.504 μm, 3.809 μm, and 6.083 μm thickness, respectively) were applied on the surface of 316L stainless steel by DC Magnetron Sputtering, followed by biocompatibility, Wettability, and scratch test investigations. The biocompatibility was determined through cell culture experiments (1, 7, and 14 days) on human osteoblast MG 63 cells and showed improved cell adherence, proliferation, and differentiation compared to bare 316L SS. Despite the ability to create highly adhering coatings of both aspects, studies on adhesion using a scratch test revealed significantly better adhesion strength (7μN, 17μN, and 23μN with ±0.296 μN) at coated surfaces. The surface characteristics of the Ta-coated and bare 316L SS were characterized using various techniques such as optical microscopy, energy dispersive x-ray spectroscopy, inductively coupled plasma mass spectroscopy, and scanning electron microscopy. Based on the results, the Ta-coated 316L stainless steel is considered a promising material for orthopedic applications due to its improved biocompatibility and surface properties. © 2023 Elsevier B.V.